GENDER FLUID DAN IDENTITAS ANDROGINI DALAM MEDIA SOSIAL - Anindya, Annisa (TINGKAP, 2016)
This paper discusses gender as an increasingly melting identity. Real practice can be found in social media, where gender identity as one of the symbols in understanding the masculinity and femininity attributes of a person begins to appear in different ways. The male phenomenon that is thought to lose the identity of masculinity for using an attribute that is stereotypically used by women is often found in social media and its interactions. Media as a source of information, correlation, continuity, entertainment, and mobilization, consciously or unconsciously, has established a new perspective in describing gender identity. The identity displayed on social media no longer has to adapt the prevailing public stereotypes. In reality, gender identity is increasingly melting.Keywords : media, identity, gender, androgini